Designing and developing a web-based information system for incoming and outgoing letters management - Putri, Silvia Agusfiani; Dewi, Indah Kusuma; Afrina, Afrina (Journal of Computer-based Instructional Media, 2025)
This study aims to design and develop a web-based information system for incoming and outgoing letter management at the Baloi Permai Subdistrict Office to enhance administrative efficiency and service transparency. A need analysis was conducted to identify key system requirements, including data collection, processing, and functional and non-functional design. The data were collected through documentation and interviews with primary stakeholders, such as the subdistrict head and administrative staff. The findings indicate that the current manual system has several drawbacks, including the absence of an integrated system, delays in document processing, and limited public accessibility. The system was developed by using the Laravel framework employing PHP and MySQL to ensure efficient development and maintenance. Unified Modeling Language (UML) was applied, incorporating Use Case, Activity, Sequence, and Class diagrams to illustrate user interactions. Black-box testing was conducted to assess system functionality, confirming its ability to streamline correspondence management with key features, such as user management, document tracking, and report generation. The system implementation is expected to improve record accuracy, accelerate document processing, and enhance public accessibility. Additionally, it is potential to be adopted by other government institutions as a digital solution for administrative management.